Effects of Multicomponent and Multiprofessional Interventions on Cardiovascular and Functional Health in Hypertensive and Normotensive Older Women: A Case Study - Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background/Objectives: This study aimed to examine the effects of changes over time during multicomponent training (MCT) combined with multiprofessional interventions at different time points [baseline (T0), 12 weeks (T1), 24 weeks (T2) and 36 weeks (T3)] on body composition; blood pressure (SBP and DBP); biomarkers [fasting glucose, total cholesterol, high-density lipoprotein (HDL-c), low-density lipoprotein (LDL-c), and triglycerides]; and physical improvement [maximal isometric handgrip strength (MIHS), arm curl, 30 s chair stand, six-minute walk test (6MWT), and timed up-and-go (TUG)] in hypertensive and normotensive older women. Methods: This longitudinal and experimental study was conducted in hypertensive (n = 23, mean age 69.7 ± 7.21 years) and normotensive (n = 17, mean age 71.3 ± 5.92 years) older women, with three 90 min sessions per week for 36 weeks, including 60 min of MCT, 30 min of nutritional education (twice a week) and 30 min of psychoeducation (once a week). Results: Significant decreases in SBP at T1 and T3 and DBP at T3 were detected in both groups, and only SBP at T2 was detected in normotensive women (p < 0.05). Significant reductions in fasting glucose at T1-T2-T3 and LDL-c and total cholesterol at T3 and triglycerides at T2 were detected in hypertensive patients (p < 0.05). Significant improvements in arm curl at T1 and the 30 s chair stand at T1–T3 were observed for both groups, and improvements at T2–T3 were detected only in hypertensive patients (p < 0.05). Conclusions: MCT and multiprofessional interventions improve blood pressure, biomarkers and physical improvement in hypertensive and normotensive older women. © 2026 by the authors.